Go to sleep, monster! - Cornell, Kevin (Balzer + Bray, an imprint of Harper Collins Publishers, 2016)
Getting George to sleep is a nightmare. But getting a monster to sleep? That's an adventure
Keywords: Sleep / Juvenile fiction; Monsters / Juvenile fiction; Fear / Juvenile fiction; Bedtime / Juvenile fiction; Bedtime; Fear; Monsters; Sleep; Bilderbuch